2021
DOI: 10.3390/w13020158
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance and Invasion Dynamics of Alien Fish Species Linked to Chemical Conditions, Ecosystem Health, Native Fish Assemblage, and Stream Order

Abstract: The incidence and dispersal of invasive alien fish species (IAFS) have ecological impacts on biodiversity and environmental health at regional to global scales. We identified links between the presence of largemouth bass (Lb) and bluegill (Bg), and selected indicators of environmental water quality, trophic and tolerance guilds, ecological health factors, and stream order. We used the data collected from national biomonitoring study sites in four major rivers of South Korea. IAFS occurred in eutrophic waters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…The increasing trend in CHL-a's higher values indicated that the risk of chlorophyll-a for drinking water repeatedly reached moderate levels (more than 10 µg/L) from August to November [53]. The findings showed the nutrient loadings from watersheds caused by extreme rainfall events that increased the algal CHL-a growth [21,[54][55][56]. The increasing TSS levels, BOD, TP, and CHL-a during the flood years declined, indicating intensive rainfall mediated dilution [20,46,57,58].…”
Section: Role Of Monsoon and Water Chemistry Variabilitymentioning
confidence: 99%
“…The increasing trend in CHL-a's higher values indicated that the risk of chlorophyll-a for drinking water repeatedly reached moderate levels (more than 10 µg/L) from August to November [53]. The findings showed the nutrient loadings from watersheds caused by extreme rainfall events that increased the algal CHL-a growth [21,[54][55][56]. The increasing TSS levels, BOD, TP, and CHL-a during the flood years declined, indicating intensive rainfall mediated dilution [20,46,57,58].…”
Section: Role Of Monsoon and Water Chemistry Variabilitymentioning
confidence: 99%
“…as blooms could also disrupt critical food-web processes, be potentially toxic, and are linked to eutrophication [19,28]. Therefore, investigating the consequences of various water chemistry pressures essentially includes trophic state assessment, physicochemical changes, and unprecedented damage to freshwater biodiversity [29][30][31]. Furthermore, deteriorating water quality could alter the typical structure and functioning of the aquatic ecosystems by directly or indirectly influencing the reservoir's response to changing inclusive environmental conditions [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…PC2 in the drought years showed a positive correlation with the nutrient ratio, BOD/COD, and inflow, and a negative correlation with TP. These correlation patterns appeared to occur mostly in the pre-monsoon period, and seemed to indicate the possibility that some COD might be internally produced in the period [75]. PC2s of the drought and the flood years showed strong correlations with inflow, outflow, and precipitation, and appeared to indicate hydrological processes in association with strong monsoon rainfall.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 86%